'Their life in your hands': the experiences of prison-based psychologists conducting risk assessments with indeterminate sentenced prisoners in the United Kingdom. Issue 4 (20th April 2020) - Shingler, Jo; Sonnenberg, Stefanie J.; Needs, Adrian
ABSTRACT: Assessing prisoners' risk of recidivism and making risk-management recommendations is central to the work of prison-based psychologists. Risk assessment is particularly crucial when it involves indeterminate sentenced prisoners: psychologists' recommendations have potentially significant consequences both for prisoners and the public. However, little is known about psychologists' experiences of conducting such high stakes risk assessments. This paper reports the results of an exploration of psychologists' experiences, via interviews and discussions with qualified, prison-based psychologists. Analysis using Grounded Theory methods identified one super-ordinate category of meaning, namely The Challenging Context of Risk Assessment, which comprised two sub-categories: (1) pressure of limited resources and (2) pressure of the environment. An additional major category, Risk Assessment as a Weighty Task, comprised three sub-categories: psychologists described (1) a weight of responsibility relating to the magnitude and range of their responsibilities; (2) a weight of expectation from colleagues to provide solutions, and (3) the trainee dilemma associated with the need to balance development of trainee psychologists' competence in risk assessment with being held accountable for their work . Understanding qualified psychologists' experiences of undertaking risk assessments with indeterminate sentenced prisoners can facilitate improvements and build on areas of existing good practice.